Activated carbon (AC) production from spent mushroom substrate (SMS) from frozen food industry - Muhamad Adib, Rinalto (2016)
Agriculture Industry in Malaysia has evolve entirely over the last decade due to the advancement in science and technology in these modern era. Globally, mushroom trade has shown an increasing trend over the last three decades. Nevertheless, Malaysia’s mushroom industry had also shown an upward trend recently. Thus, the increasing of mushroom production in Malaysia also has led to the increase of the mushroom waste such as the spent mushroom substrate (SMS). It is estimated that for every kilogram of mushroom grown, about 4 to 5 kg of SMS is being produced. Since the SMS has high potential to be converted to activated carbon (AC) by using the pyrolysis method and chemical activation simultaneously, thus these study is crucial to identify whether it is suitable for the AC derived from these SMS to be used in the daily life or industrial application especially in the waste water treatment as the AC has a very excellent adsorption properties. In order to characterize the AC produce, the Surface area analyzer (BET), Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analyzer (TGA) is use to analyze the AC’s properties. It is expected that the AC produce from the SMS is suitable to be use in the industrial waste water treatment and other application since the SMS have high content of carbon compound that can be converted to AC by pyrolysis and chemical activation method.